2010
DOI: 10.1177/1084822309360380
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Depression Among Older Adults Referred to Home Care Services: A Single-Item Depression Screener Versus the Geriatric Depression Scale

Abstract: Older adults requiring home care service have a high risk of depression. Instruments for detecting depression among older adults, however, are often too long and detailed for easy administration by nontrained staff in large service-based settings.This study examined the measurement properties (test—retest reliability, concurrent validity, and cross-modality correspondence) of a single-item screener for depressive symptoms among older adults receiving home care services. Reliability was assessed (n = 65) by adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…For self-rated depression, as in several other studies [ 3 , 9 , 77 ], a single-item measure was used. Previous research about the reliability and validity of single-item depression measures has found that results can vary between different contexts and populations [ 91 ]. However, there has been relatively little research on these measures in the general adult population.…”
Section: Discussionmentioning
confidence: 99%
“…For self-rated depression, as in several other studies [ 3 , 9 , 77 ], a single-item measure was used. Previous research about the reliability and validity of single-item depression measures has found that results can vary between different contexts and populations [ 91 ]. However, there has been relatively little research on these measures in the general adult population.…”
Section: Discussionmentioning
confidence: 99%
“…This absence of stimulation can have negative consequences. For example, a third of community-dwelling older persons report feeling lonely and nearly half screen for depression (Cohen-Mansfield & Frank 2008, McCormack et al 2011. Over 60% of community-dwelling persons with dementia show behavioural symptoms, such as agitation, aggression, psychosis, anxiety and depression (Lyketsos et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Home care recipients’ ratings of their opportunities for activities were significantly lower than residents in nursing homes [ 11 ]. Forty-two per cent of Australians referred to home care screened positive for depression [ 12 ], and similarly 43% of American home care clients met DSM-IV criteria for depression [ 13 ]. Sixty per cent of community dwelling persons with dementia have behavioural disturbances [ 14 ].…”
Section: Introductionmentioning
confidence: 99%